2018
DOI: 10.1111/psyp.13081
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol hangover impacts learning and reward processing within the medial‐frontal cortex

Abstract: It is common knowledge that alcohol intoxication impairs motor coordination, judgment, and decision making. Indeed, an abundance of literature links intoxication to impaired cognitive control that leads to accidents and injury. A broadening body of research, however, suggests that the impact of alcohol may continue beyond the point of intoxication and into the period of alcohol hangover. Here, we examined differences in the amplitude of reward positivity-a component of the human ERP associated with learning-be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 51 publications
0
10
1
Order By: Relevance
“…Indeed, they were not forced to go to the laboratory to be tested on a specific day, but they could spontaneously reach the laboratory on a day/time of their choice (e.g., on break between two lectures). Surprisingly, the students tested showed a quite high level of hangover severity (AHSS = 4.11), compared to previous studies ( Penning et al, 2013 ; Verster et al, 2014 ; Howse et al, 2018 ), suggesting that even a relatively severe hangover did not prevent participants from going to the university and carrying out their scheduled activities. If this generalized to the majority of hungover students, they would be potentially eligible – among all the other students – for psychological experiments and could consequently affect the internal validity of the same experiments.…”
Section: Discussioncontrasting
confidence: 81%
“…Indeed, they were not forced to go to the laboratory to be tested on a specific day, but they could spontaneously reach the laboratory on a day/time of their choice (e.g., on break between two lectures). Surprisingly, the students tested showed a quite high level of hangover severity (AHSS = 4.11), compared to previous studies ( Penning et al, 2013 ; Verster et al, 2014 ; Howse et al, 2018 ), suggesting that even a relatively severe hangover did not prevent participants from going to the university and carrying out their scheduled activities. If this generalized to the majority of hungover students, they would be potentially eligible – among all the other students – for psychological experiments and could consequently affect the internal validity of the same experiments.…”
Section: Discussioncontrasting
confidence: 81%
“…In addition, some studies have focused on women only [45], while others did not mention the sex of their participants [46,47]. Moreover, several studies on cognitive performance included both men and women but omitted any statistical analysis on possible sex effects [6,48,49,50,51,52,53,54,55], leaving it unknown whether sex differences were either absent or not investigated. Up to now, six controlled studies examining performance on a variety of cognitive, psychomotor, and memory tests found no significant sex differences on any of the administered tests [56,57,58,59,60,61], and two other studies reported no significant sex differences in driving performance [4,62].…”
Section: Introductionmentioning
confidence: 99%
“…Two studies, which included measures on subjective feelings during hangover, only found increases in fatigue or arousal , therefore it was unclear if participants were experiencing a hangover. Seven studies failed to measure BAC at testing , and two studies which did measure BAC showed that participants achieved BAC > 0.02% . Two studies included other treatments in their research design .…”
Section: Resultsmentioning
confidence: 99%